PENGUATAN SISTEM PENDIDIKAN SDM DALAM PEMBANGUNAN PERTANIAN: AGRIBISNIS DI MATA PEMUDA - Prayoga, Kadhung; Nurfadillah, Suryani; Riezky, Adietya Muhammad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
The interest of students to continuing their study into university level is very high, one of which is the department of agribusiness. This certainly contradicts with the low interest of young people to become farmers. Because of this phenomena, then this paper want to discuss how students' knowledge, judgment, and perceptions of agribusiness as they were high school students and as college students now. This research used descriptive method with a quantitative approach and survey as its research technique. The samples for this study were 48 new students of 2018 Agribusiness Program, Faculty of Animal and Agricultural Sciences, Diponegoro University that taken by convenience sampling. Primary data was obtained by distributing questionnaires using google form on December 9-22, 2018. While secondary data was obtained from literature studies. The collected data was then analyzed descriptively. The majority of respondents have minimal knowledge regarding agribusiness program when they were in high school, some even did not know at all. They can only perceive agribusiness as a study program related to business and economic in agriculture. The majority of respondents chose agribusiness just for trying their luck, but there were also those based on desire, passion, opportunities, and parents’ advises. After becoming a Agribusiness student, they saw agribusiness as an attractive department because it combines natural and social science. Massive socialization is needed to increase public understanding and interest in agribusiness program.